Dietary vegetable oils inclusion on the performance, hormonal levels and hsp 70 gene expression in broilers under heat stress (Acta Scientiarum. Animal Sciences, 2019)
The aim of the present study was to compare the effects of unsaturated and saturated oils on the performance, hormonal levels and hsp gene expression in broiler chickens exposed to heat stress. 300 one-day male broiler chicks were assigned to 4 treatments (Diets containing palm, corn, linseed or olive oils) with 5 replicates. At day 28 of age, 2 chickens were removed from each replicate, then blood samples and liver tissue samples were collected for analyses. Feeding linseed and olive oil reduced feed conversion ratio compared to corn and palm oils. The lowest level of insulin was for chickens fed linseed oil and corn oil. The highest level of corticosterone was found in chickens fed palm oil and the lowest level was for those received linseed oil. Chickens received linseed and corn oils had the highest levels of T3 and T4 and those fed palm and olive oils had the lowest levels. The highest HSP 70 gene expression was for chickens fed diet containing olive and linseed oils and the lowest one was for those fed corn and palm oils. It was concluded that olive oil and linseed oil could improve performance and heat tolerance of chickens under heat stress.